BK channel β1 and β4 auxiliary subunits exert opposite influences on escalated ethanol drinking in dependent mice - Kreifeldt, Max; Le, David; Treistman, Steven N.; Koob, George; Contet, Candice (Frontiers in Integrative Neuroscience, 2013)
Large conductance calcium-activated potassium (BK) channels play a key role in the control of neuronal activity. Ethanol is a potent activator of BK channel gating, but how this action may impact ethanol drinking still remains poorly understood. Auxiliary β subunits are known to modulate ethanol-induced potentiation of BK currents. In the present study, we investigated whether BK β1 and β4 subunits influence voluntary ethanol consumption using knockout mice. In a first experiment, mice were first subjected to continuous two-bottle choice (2BC) and were then switched to intermittent 2BC, which progressively increased ethanol intake as previously described in wildtype mice. BK β1 or β4 subunit deficiency did not affect ethanol self-administration under either schedule of access. In a second experiment, mice were first trained to drink ethanol in a limited-access 2BC paradigm. BK β1 or β4 deletion did not affect baseline consumption. Weeks of 2BC were then alternated with weeks of chronic intermittent ethanol (CIE) or air inhalation. As expected, a gradual escalation of ethanol drinking was observed in dependent wildtype mice, while intake remained stable in non-dependent wildtype mice. However, CIE exposure only produced a mild augmentation of ethanol consumption in BK β4 knockout mice. Conversely, ethanol drinking increased after fewer CIE cycles in BK β1 knockout mice than in wildtype mice. In conclusion, BK β1 or β4 did not influence voluntary ethanol drinking in non-dependent mice, regardless of the pattern of access to ethanol. However, deletion of BK β4 attenuated, while deletion of BK β1 accelerated, the escalation of ethanol drinking during withdrawal from CIE. Our data suggest that BK β1 and β4 subunits have an opposite influence on the negative reinforcing properties of ethanol withdrawal. Modulating the expression, distribution or interactions of BK channel auxiliary subunits may therefore represent a novel avenue for the treatment of alcoholism.